PERBEDAAN KECEMASAN DAN LAMA BERSALIN, ANTARA IBU PRIMIPARA YANG MENERIMA DAN TIDAK MENERIMA PENDAMPINGAN DOA DAN DUKUNGAN PSIKOFISIOLOGIS SAAT BERSALIN - Diponegoro, Ahmad Muhammad (Universitas Ahmad Dahlan, 2009)
Aims: to investigate the role of religiousity and psychophysiologicalsupports during labor in primipara.Method: Women under 35 during gestation weeks 36-42 screenedfor traumatic symptoms living in urban area of Yogyakarta, 50 metinclusion criteria and were randomized into an intervention (n=26) andcontrol (n-24) group. This research was done experimentally. Theintervention included improving their religiousity, psychological andphysiological supports.Result: From data analysis we found that intervention group womenreported low relative risk of anxiety, shortened labor duration.Key words: primipara, psychophysiological supports,